2000
DOI: 10.1289/ehp.0010867
|View full text |Cite
|
Sign up to set email alerts
|

The role of selenium in iodine metabolism in children with goiter.

Abstract: Possible interactions between selenium and iodine metabolism were investigated in 7- to 16-year-old children with goiter (n = 136) living in southeastern Poland in iodine-deficient areas influenced by a sulfur industry. The Se-iodine interactions in these children were compared to the interactions in children from outside of that region (n = 38). Blood selenium (BSe) concentration and plasma glutathione peroxidase activity were much lower in the study group (64.1 +/- 15.7 microg/L; 111.0 +/- 27.6 U/L) than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…In formula-fed preterm infants a gender-related effect on Se metabolism was reported by Friel et al (1993). In Poland, a gender-linked hormonal response to concomitant Se and I deficiency in older children (7 -16 years) with goitre was reported by Zagrodzki et al (2000). In breast-fed infants, Yoshinaga et al (1991) showed a significant association between milk Se and gender, but Cumming et al (1992b ) reported no significant difference in breast-milk Se due to the infant's gender.…”
Section: Selenium Interactions and Breast-feedingmentioning
confidence: 97%
“…In formula-fed preterm infants a gender-related effect on Se metabolism was reported by Friel et al (1993). In Poland, a gender-linked hormonal response to concomitant Se and I deficiency in older children (7 -16 years) with goitre was reported by Zagrodzki et al (2000). In breast-fed infants, Yoshinaga et al (1991) showed a significant association between milk Se and gender, but Cumming et al (1992b ) reported no significant difference in breast-milk Se due to the infant's gender.…”
Section: Selenium Interactions and Breast-feedingmentioning
confidence: 97%
“…The beneficial effects of iodine on morphological parameters of animal blood are evidenced by the works of Lima et al, 1989;Moreno-Reyes et al, 2003;Zagrodzki et al, 2000. Conclusion Feed iodine supplements had a positive effect on hematopoietic organs: their usage helped to improve the overall condition of the blood: the number of red blood cells has increased by 1.4-6.7%, hemoglobin-by 5.3-8.8% and leukocytes-by 4.4-7.6%.…”
Section: Resultsmentioning
confidence: 90%
“…In our study, no association was found between selenium and iodine, and thyroid hormones (Table 5). However, several studies indicated that effects of selenium deficiency or excess on thyroid hormone biosynthesis in severe ID were more likely to be more pronounced than in mild ID [40][41][42][43]. Although, according to Rasmussen et al (2011), optimal selenium status might help to prevent iodine deficiency disorders (IDD), particularly thyroid gland enlargement.…”
Section: Methodsmentioning
confidence: 99%